High-temperature-resistant high-toughness controllable degradation polylactic acid material and preparation method thereof

By using a combination of polylactic acid-polyurethane block copolymer and activated talc powder in PLA straw, combined with high-speed mixing and twin-screw extruder processes, the problems of insufficient performance of PLA straw at high and low temperatures and uncontrollable degradation cycles are solved, and the material's high heat resistance, low temperature toughness and controllable degradation cycles are achieved.

CN120118494APending Publication Date: 2025-06-10JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510491669.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing polylactic acid (PLA) straws are insufficient heat resistance at high temperatures, have high brittleness at low temperatures, and their degradation cycle is uncontrollable.

Method used

Using a combination of 40%-60% polylactic acid, 10%-20% polylactic acid-polyurethane block copolymer, 20%-40% active talc powder and 1%-5% additives, the premixed material is formed and granulated through high-speed mixing and melt blending of twin-screw extruder. The premixed material is formed and granulated, thereby improving the heat resistance, low temperature toughness and degradation cycle of the material.

Benefits of technology

The heat resistance temperature of the material is significantly improved to ≥90℃, the elongation of break at -20℃ is ≥30%, and the degradation period is controlled between 6-12 months, solving the problem of insufficient performance of existing PLA straws at high and low temperatures and uncontrollable degradation period.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant high-toughness controllable degradation polylactic acid material, which is prepared from the following components in percentage by mass: 40 to 60 percent of polylactic acid, 10 to 20 percent of polylactic acid-polyurethane block copolymer, 20 to 40 percent of active talcum powder and 1 to 5 percent of auxiliaries. The heat resistance of the material can be remarkably improved; the low-temperature toughness of the material is obviously improved; and the degradation period of the material is controllable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polylactic acid materials, and in particular to a high-temperature resistant, high-toughness, controllably degradable polylactic acid material and a preparation method thereof. Background Art

[0002] Traditional disposable plastic straws are mainly made of polyethylene (PE) or polypropylene (PP), which have a degradation cycle of hundreds of years and cause serious pollution to the ecological environment. Their use has been explicitly restricted by many countries and regions around the world. Currently, polylactic acid (PLA) straws are the main alternative. Although they are biodegradable, their performance still has the following significant defects:

[0003] 1. Insufficient heat resistance: PLA molecular chains are very rigid and have a slow crystallization rate. Under normal processing conditions, the crystallinity is less than 8%, resulting in the Vicat softening point of existing PLA straws being only 59-70°C, which cannot meet the long-term use requirements of hot drinks such as coffee and tea at a temperature of 75-95°C.

[0004] 2. The contradiction between low-temperature brittleness and interface compatibility: The main components of the PLA hot drink straws currently on the market are the PLA / PBS / talcum powder system. Due to the polarity difference between PLA and PBS, the phase separation occurs. The elongation at break of the material at -5°C is only 8.3%, and it is easy to crack in winter.

[0005] 3. The degradation cycle is uncontrollable: It takes 12-24 months for pure PLA to completely degrade in the natural environment. However, the modified system filled with talcum powder or blended with PBS has a higher crystallinity and the degradation time is further extended to 18-30 months, which is seriously out of line with the short-term use scenario of food packaging.

[0006] The above problems are caused by the high rigidity of PLA molecular chain and slow crystallization rate (half crystallization time t 1 / 2 >15min), combined with the weak interface bonding between inorganic fillers and PLA matrix in existing modification technologies and the phase separation tendency of incompatible toughening agents, lead to the formation of micron-level defects inside the material, which ultimately manifests as a synergistic failure of heat resistance, toughness and degradation performance. Therefore, a material with high heat resistance of Vicat softening point ≥90℃, elongation at break of -20℃ ≥25% and notched impact strength >10kJ / m 2 PLA straw modified materials with excellent low-temperature toughness and a controllable degradation cycle of 6-12 months have become technical problems that need to be urgently solved in this field. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a high-temperature resistant, high-toughness, controllable degradation polylactic acid material and its preparation method to solve the technical problems of insufficient high-temperature heat resistance, low-temperature toughness, and uncontrollable degradation period of PLA materials in the prior art.

[0008] The present invention provides a high-temperature resistant, high-toughness, controllable degradation polylactic acid material, which includes, by mass percentage: 40%-60% of polylactic acid, 10%-20% of polylactic acid-polyurethane block copolymer, 20%-40% of active talc powder, and 1%-5% of additives.

[0009] Further, the surface of the active talc powder is treated with a coupling agent.

[0010] Further, the coupling agent is: aluminate, titanate or phosphate ester.

[0011] Further, the dosage of the coupling agent is 1%-5% of the mass of the talc powder.

[0012] Further, the additives include: compatibilizer and dispersant.

[0013] Further, the compatibilizer is: maleic anhydride grafted; the dispersant is: calcium stearate.

[0014] The present invention also provides a preparation method of a high-temperature resistant, high-toughness, controllable degradation polylactic acid material, which includes the following steps:

[0015] Step 1: Add polylactic acid, polylactic acid-polyurethane block copolymer, active talc powder and additives into a high-speed mixer according to the ratio, and mix at 50-80°C for 5-15 minutes to make the materials evenly dispersed to form a premix.

[0016] Step 2: Feed the premix into a twin-screw extruder and carry out melt blending and chain extension reaction at a melting temperature of 170-190°C.

[0017] Step 3: Extrude and pelletize to obtain a high-temperature resistant, high-toughness, controllable degradation polylactic acid material.

[0018] Further, in the step 2, the screw speed range is: 200-450 rpm; the temperature zones are: the front section, the middle section and the end section. The temperature range of the front section is: 170-173°C; the temperature range of the middle section is: 180-183°C; the temperature range of the end section is: 185-190°C; the melt blending time is 4-8 minutes, and the melt pressure is greater than or equal to 6 Mpa; the vacuum degree of the vacuum devolatilization device at the end of the screw is less than or equal to -0.08 MPa.

[0019] Further, in the step 3, the diameter of the extruded and granulated particles is less than or equal to 5 mm; the moisture content of the dried particles is less than or equal to 500 ppm; the temperature for cooling and pelletizing is less than or equal to 50 °C.

[0020] The present invention also provides a straw prepared from a high-temperature resistant, high-toughness and controllable degradation polylactic acid material.

[0021] Further, the tensile strength of the straw is greater than or equal to 35 MPa; the elongation at break at -20 °C is greater than or equal to 30%; the heat resistance temperature is greater than or equal to 90 °C.

[0022] Beneficial effects of the present invention:

[0023] The present invention can significantly improve the heat resistance of the material: the heat resistance temperature of the modified material ≥ 90 °C, no deformation after soaking in 90 °C hot water for 30 minutes, and can withstand boiling water grade hot drinks;

[0024] The present invention can significantly improve the low-temperature toughness of the material: the notched impact strength of the modified material at -20 °C ≥ 12 kJ / m 2 , the elongation at break ≥ 30%, solving the problem of brittle cracking in winter, superior to existing materials, and improving by 40% - 100%;

[0025] The present invention can make the degradation period of the material controllable: by adjusting the ratio of polylactic acid - polyurethane block copolymer to active talc powder, the degradation period can be controlled within 6 - 12 months. Description of the drawings Detailed implementation manners

[0026] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Apparently, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.

[0027] The following further clarifies the present invention with specific embodiments. Those skilled in the art should understand that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. Modifications in various equivalent forms of the present invention all fall within the scope defined by the appended claims of this application.

[0028] A specific embodiment of the present invention provides a high-temperature resistant, high-toughness and controllable degradation polylactic acid material, which includes, by mass percentage: 40% - 60% of polylactic acid (PLA), 10% - 20% of polylactic acid - polyurethane block copolymer (PLA - PU), 20% - 40% of active talc powder, and 1% - 5% of additives.

[0029] Among them, the surface of the active talcum powder is treated with a coupling agent, and the coupling agent is: aluminate, titanate or phosphate. The dosage of the coupling agent is 1%-5% of the mass of the talcum powder, and the treatment time is: 0.5-2 hours;

[0030] The additives include: a compatibilizer and a dispersant. The compatibilizer is: maleic anhydride grafted; the dispersant is: calcium stearate.

[0031] The specific embodiment of the present invention also provides a preparation method of a high-temperature resistant and high-toughness controllable degradation polylactic acid material, which includes the following steps:

[0032] Step 1: Add polylactic acid, polylactic acid-polyurethane block copolymer, active talcum powder and additives into a high-speed mixer according to the ratio, and mix at 50-80 °C for 5-15 minutes to uniformly disperse the materials to form a premix;

[0033] Step 2: Feed the premix into a twin-screw extruder and carry out melt blending and chain extension reaction at a melting temperature of 170-190 °C,

[0034] Among them, the screw speed range is: 200-450 rpm; the temperature zones are: the front section, the middle section and the end section. The temperature range of the front section is: 170-173 °C; the temperature range of the middle section is: 180-183 °C; the temperature range of the end section is: 185-190 °C; the melt blending time is 4-8 minutes, and the melt pressure is greater than or equal to 6 Mpa; a vacuum devolatilization device is configured at the end of the screw, and the vacuum degree of the vacuum devolatilization device is less than or equal to -0.08 MPa;

[0035] Step 3: Extrusion granulation to obtain a high-temperature resistant and high-toughness controllable degradation polylactic acid material,

[0036] Among them, the particle diameter of the extrusion granulation is less than or equal to 5 mm; the moisture content after particle drying is less than or equal to 500 ppm; the temperature for cooling and pelletizing is less than or equal to 50 °C.

[0037] The straw prepared by the preparation method has a tensile strength greater than or equal to 35 MPa; the elongation at break at -20 °C is greater than or equal to 30%; the heat resistance temperature is greater than or equal to 90 °C.

[0038] 40% to 60% of polylactic acid (PLA) and 10% to 20% of polylactic acid-polyurethane block copolymer (PLAU) are melt-blended and compounded. The flexible phase is introduced by the polyurethane soft segment of PLAU (such as polyether / polyester polyol segment), effectively toughening the PLA matrix and suppressing low-temperature brittleness; at the same time, through the in-situ chain extension reaction (melt pressure ≥ 6 MPa) during the twin-screw extrusion process, the molecular weight of PLA (weight-average molecular weight Mw ≥ 150,000 g / mol) and the crosslinking degree are increased to form a blend system with both high toughness (elongation at break at -20 °C ≥ 30%) and heat resistance (Vicat softening point ≥ 90 °C);

[0039] Introduce 20% to 40% of active talc powder with a particle size of 1 - 10 μm surface-treated with a coupling agent (aluminate, titanate or phosphate), which has a flaky morphology with an aspect ratio > 20 and a thickness ≤ 0.1 μm. Enhance the crystallization performance of the material through the oriented arrangement of the lamellae, and significantly increase the heat-resistant temperature;

[0040] Add 1% to 3% of a compatibilizer (maleic anhydride grafted) and 0.5% to 2% of a dispersant (calcium stearate). Improve the filler dispersion through the hydrogen bond interaction between the polar group (maleic anhydride grafted) and the hydroxyl groups on the talc surface; at the same time, calcium stearate ensures the stability of the twin-screw extrusion process (screw speed 200 - 450 rpm, temperature zone 170 - 190 °C) by reducing the melt viscosity.

[0041] The following is illustrated by examples:

[0042] Example 1: High heat-resistant formulation

[0043] Formulation composition:

[0044] Polylactic acid (PLA): 55%;

[0045] Polylactic acid-based polyurethane (PLAU): 10%;

[0046] Active talc powder: 30%, treated with aluminate coupling agent, and the dosage of the coupling agent is 3% of the mass of the talc powder;

[0047] Compatibilizer: maleic anhydride grafted, 3%;

[0048] Dispersant: calcium stearate, 2%;

[0049] Preparation method:

[0050] Mix PLAU and active talc powder in a high-speed mixer at 80 °C for 10 minutes;

[0051] Add PLA, compatibilizer and dispersant, and continue to mix at high speed for 8 minutes;

[0052] Pelletize through a co-rotating twin-screw extruder. Among them, the screw diameter is 35 mm, the length-diameter ratio is 48:1, the screw speed is 300 rpm, and the temperature zone is:

[0053] Feeding section: 170 - 173 °C;

[0054] Melting section: 180 - 183 °C;

[0055] Mixing section: 185 - 188 °C;

[0056] Homogenization section: 185 - 190 °C;

[0057] Melt pressure: 6.5 MPa;

[0058] Vacuum devolatilization: Vacuum degree -0.09 MPa;

[0059] Pelletizing: Using a water ring pelletizing system (water temperature 15 °C), pellet diameter 2 mm, water content after drying 280 ppm (drying temperature 55 °C);

[0060] Performance test results:

[0061] Tensile strength: 42 MPa, meeting the requirements of GB / T 1040.1-2018;

[0062] Elongation at break at -20 °C: 31%, meeting the requirements of GB / T 1040.3-2006;

[0063] Notched impact strength at -20 °C: 13.5 kJ / m2, meeting the requirements of GB / T 1843-2008;

[0064] Heat resistance temperature: 95 °C;

[0065] Degradation period: 10 months, meeting the requirements of the composting conditions of GB / T 19277.1-2011.

[0066] Example 2: High toughness formulation

[0067] Formulation composition:

[0068] Polylactic acid (PLA): 45%;

[0069] Polylactic acid-based polyurethane (PLAU): 20%;

[0070] Activated talc powder: 29%, treated with titanate coupling agent, the dosage of the coupling agent is 2% of the mass of the talc powder; Compatibilizer: maleic anhydride grafted, 4%;

[0071] Dispersant: calcium stearate, 2%;

[0072] Preparation method:

[0073] Same as Example 1, adjust the screw speed to 350 rpm to optimize the dispersion effect;

[0074] Performance test results:

[0075] Tensile strength: 38 MPa, meeting the requirements of GB / T 1040.1-2018;

[0076] Elongation at break at -20 °C: 37%, meeting the requirements of GB / T 1040.3-2006;

[0077] Notched impact strength at -20°C: 14.2 kJ / m2, meeting the requirements of GB / T 1843-2008;

[0078] Heat resistance temperature: 91°C;

[0079] Degradation period: 8 months, meeting the requirements of the composting conditions of GB / T 19277.1-2011.

[0080] Example 3: High-temperature and high-toughness balanced formula

[0081] Formulation composition:

[0082] Polylactic acid (PLA): 48%;

[0083] Polylactic acid-based polyurethane (PLAU): 18%;

[0084] Activated talc powder: 28%, treated with a phosphate ester coupling agent, and the dosage of the coupling agent is 2.5% of the mass of the talc powder; compatibilizer: maleic anhydride grafted, 3.5%;

[0085] Dispersant: calcium stearate, 2.5%;

[0086] Preparation method:

[0087] Pretreatment: Treat the talc powder and the phosphate ester coupling agent in a high-speed mixer at 80°C for 1.5 hours; melt blending: Blend PLA, PLAU, the pretreated talc powder and other additives in a high-speed mixer for 5 minutes;

[0088] Extrusion granulation: Granulate using a co-rotating twin-screw extruder, where the screw diameter is 35 mm, the length-diameter ratio is 42:1, and the screw speed is 280 rpm;

[0089] The specific temperature zone settings are the same as in Example 1;

[0090] Melt pressure: 6.8 MPa;

[0091] Vacuum degree: -0.08 MPa;

[0092] Particle diameter: 2.2 mm, moisture content 300 ppm;

[0093] Performance test results:

[0094] Tensile strength: 40.5 MPa, meeting the requirements of GB / T 1040.1-2018;

[0095] Elongation at break at -20°C: 35%, meeting the requirements of GB / T 1040.3-2006;

[0096] Notched impact strength at -20°C: 12.8 kJ / m2, meeting the requirements of GB / T 1843-2008;

[0097] Heat resistance temperature: 93°C;

[0098] Degradation period: 9 months, meeting the requirements of the composting conditions of GB / T 19277.1-2011.

[0099] Comparative Example 1

[0100] Formulation composition:

[0101] Polylactic acid (PLA): 60%;

[0102] Ordinary talc powder (untreated): 35%;

[0103] Compatibilizer: maleic anhydride grafted, 3%;

[0104] Dispersant: calcium stearate, 2%;

[0105] Preparation method: the same as that of Example 1, but the talc powder is not treated with a coupling agent;

[0106] Performance test results:

[0107] Tensile strength: 26 MPa;

[0108] Elongation at break at -20°C: 12%;

[0109] Notched impact strength at -20°C: 2.5 kJ / m2

[0110] Heat resistance temperature: 72°C, severely deformed after soaking in hot water at 90°C;

[0111] Degradation period: 14 months.

[0112] Comparative Example 2

[0113] Formulation composition:

[0114] Polylactic acid (PLA): 50%;

[0115] Ordinary talc powder (untreated): 30%;

[0116] Polylactic acid-based polyurethane (PLAU): 15%;

[0117] Compatibilizer: maleic anhydride grafted, 3%;

[0118] Dispersant: calcium stearate, 2%;

[0119] Preparation method: the same as that of Example 1;

[0120] Performance test results:

[0121] Tensile strength: 28 MPa;

[0122] Elongation at break at -20°C: 14%;

[0123] Notched impact strength at -20°C: 7.8 kJ / m2

[0124] Heat resistance temperature: 85°C, partial deformation after soaking in 90°C hot water;

[0125] Degradation period: 13 months.

[0126] It can be seen from the examples and comparative examples that the heat resistance temperature of the modified material of the present invention is ≥ 90°C, there is no deformation after soaking in 90°C hot water for 30 minutes, and it can withstand boiling water-level hot drinks; the notched impact strength of the material at -20°C is ≥ 12 kJ / m 2 , the elongation at break is ≥ 30%, solving the problem of brittle fracture in winter, which is superior to the existing materials and has been improved by 40% - 100%; by adjusting the ratio of polylactic acid - polyurethane block copolymer to active talc powder, the degradation period can be controlled within 6 - 12 months.

[0127] Although the embodiments of the present invention have been described, those skilled in the art can make various modifications and variations without departing from the spirit and scope of the present invention, and such modifications and variations all fall within the scope defined by the appended claims.

Claims

1. A high temperature resistant, high toughness, controllably degradable polylactic acid material, characterized in that: The invention comprises, by mass percentage, 40%-60% of polylactic acid, 10%-20% of polylactic acid-polyurethane block copolymer, 20%-40% of active talc powder and 1%-5% of auxiliary agent.

2. The high temperature resistant, high toughness, controllably degradable polylactic acid material according to claim 1, characterized in that: The surface of the active talc is treated with a coupling agent.

3. The high temperature resistant, high toughness, controllably degradable polylactic acid material according to claim 2, characterized in that: The coupling agent is: aluminate, titanate or phosphate.

4. The high temperature resistant, high toughness, controllably degradable polylactic acid material according to claim 2 or 3, characterized in that: The amount of the coupling agent used is 1%-5% of the mass of talc.

5. The high temperature resistant, high toughness and controllably degradable polylactic acid material according to claim 1, characterized in that: The auxiliary agent includes: a compatibilizer and a dispersant.

6. The high temperature resistant, high toughness and controllably degradable polylactic acid material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted; the dispersant is calcium stearate.

7. A method for preparing the high temperature resistant, high toughness and controllably degradable polylactic acid material as claimed in any one of claims 1 to 6, characterized in that: The steps include: Step 1: Add polylactic acid, polylactic acid-polyurethane block copolymer, active talc and additives into a high-speed mixer according to the proportion, and mix at 50-80° C. for 5-15 minutes to evenly disperse the materials to form a premix; Step 2: feeding the premix into a twin-screw extruder for melt blending and chain extension reaction at a melt temperature of 170-190°C; Step 3: Extrusion granulation to obtain high temperature resistant, high toughness and controllably degradable polylactic acid material.

8. The method for preparing the high temperature resistant, high toughness and controllably degradable polylactic acid material according to claim 7, characterized in that: In the step 2, the screw speed range is: 200-450rpm; the temperature zones are: front section, middle section and end section, the temperature range of the front section is: 170-173°C; the temperature range of the middle section is: 180-183°C; the temperature range of the end section is: 185-190°C; the melt blending time is 4-8 minutes, and the melt pressure is greater than or equal to 6MPa; the vacuum degree of the vacuum devolatilization device at the end section of the screw is less than or equal to -0.08MPa; In the step 3, the diameter of the extruded granules is less than or equal to 5 mm; the moisture content of the granules after drying is less than or equal to 500 ppm; and the temperature for cooling and granulating is less than or equal to 50° C.

9. A straw made of the high temperature resistant, high toughness and controllably degradable polylactic acid material as claimed in any one of claims 1 to 6.

10. The method for preparing the high temperature resistant, high toughness and controllably degradable polylactic acid material according to claim 9, characterized in that: The prepared straw has a tensile strength greater than or equal to 35 MPa, an elongation at break at -20°C greater than or equal to 30%, and a heat-resistant temperature greater than or equal to 90°C.

Citation Information

Cited By

  • Degradable environment-friendly suction nozzle based on PLA / PBS composite material and preparation method of degradable environment-friendly suction nozzle

    CN121343341A

  • High-barrier polylactic acid packaging material and preparation method thereof

    CN122255690A